Poétique du récit - Barthes, Roland 1915-1980; Kayser, Wolfgang 1906-1960; Booth, Wayne C. 1921-2005; Hamon, Philippe (Paris Seuil, 1977)
In its almost infinite forms, the narrative is present in all times, in all places, in all societies; the narrative begins with the very history of humanity; there is not, there has never been anywhere any people without a narrative; all classes, all human groups have their narratives, and very often these narratives are tasted in common, by men of different, even opposite, cultures: the narrative does not care about good and bad literature: international, transhistorical, transcultural, the narrative is there, like life. Specialists from several countries (France, United States, Germany) are gathered here around a common problematic: narrative, narrator, narration, character.
Keywords: Rhetoric; Literature